3D hybrid perovskite solid solutions: a facile approach for deposition of nanoparticles and thin films via B-site substitution. (19th March 2019) - Aamir, Muhammad; Mehmood, Rana Farhat; Butt, Arshad Farooq; Khan, Malik Dilshad; Malik, Mohammad Azad; Revaprasadu, Neerish; Nunzi, Jean-Michel; Sher, Muhammad; Akhtar, Javeed
Abstract : CH3 NH3 Pb1− x Cu x Br3 hybrid perovskite solid solutions as nanoparticles and thin films have been fabricated. Abstract : Mixed metal halide perovskites are gaining paramount interest due to efficient band gap tenability and improved optical properties compared to their single metal halide perovskites. It is thus valuable to investigate compositional changes in lead halide perovskites to explore energy changes. Herein, we report the synthesis of a lead to lead free hybrid perovskite solid solution (CH3 NH3 Pb1− x Cu x Br3 ) as nanoparticles and films. The increasing concentration of Cu 2+ ions in the site of the Pb 2+ ion in the perovskite shifted the diffraction peaks to a larger angle. Uniform spherically shaped nanoparticles were synthesized by a wet chemical method, the higher Cu 2+ concentration leads to agglomeration, producing sheet like morphologies. However, the deposition of thin films of CH3 NH3 Pb1− x Cu x Br3 perovskite solid solution shows that well defined morphologies begin to appear with increasing concentrations of Cu 2+ in the perovskite structure. The as-prepared bulk lead free CH3 NH3 CuBr3 perovskite shows a band gap of 1.65 eV. A blue shift in photoluminescence (PL) was observed with copper enriched hybrid perovskites.